2016
DOI: 10.1016/j.ajic.2016.04.243
|View full text |Cite
|
Sign up to set email alerts
|

Health care worker follow-up compliance after occupational bloodborne pathogens exposure: A brief report

Abstract: care worker follow-up compliance after occupational bloodborne pathogens exposure: A brief report" (2016).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…In this study, it was observed that in three (9.4%) cases, the source was positive for HIV, a mean higher than those found in the literature. A study carried out by the CDC, to analyze the WABM that occurred from 2011 to 2015, showed the value of 2.9% as an average positive source for HIV (23) . In Brazil, in a study on occupational exposures to biological material, it was found that, in 2.56% of cases, the source was positive for HIV (17) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, it was observed that in three (9.4%) cases, the source was positive for HIV, a mean higher than those found in the literature. A study carried out by the CDC, to analyze the WABM that occurred from 2011 to 2015, showed the value of 2.9% as an average positive source for HIV (23) . In Brazil, in a study on occupational exposures to biological material, it was found that, in 2.56% of cases, the source was positive for HIV (17) .…”
Section: Discussionmentioning
confidence: 99%
“…In studies carried out in several countries to assess adherence to PEP after occupational exposure, similar results were found, as in a study carried out in Denmark, in which the adherence rate was 65.5%. Moreover, a study in India had a 64.6% adherence rate, and in the United States, 62.5% (20,23,27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case-control study conducted in Brazil used information from work accident registers from 1989 to 2010 and identified 8,568 events of biological materials accidents and 2.1% involved individuals who presented no presumed risk for this occurrence (15) . This represents a major challenge for the health sector given the general population's lack of knowledge about the adoption of prophylactic behavior after exposure to biological agents, especially HIV and Hepatitis B and C (16) . These numbers are highly underreported and do not represent the true magnitude of this problem in Brazil; the low quality of the records in the information systems represented a great challenge for the planning of actions in workers' health by the Unified Health System.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study point to some imperfections in the current system for the prevention of blood-borne infections. Broadly, the problems arise due to cost savings, where costs associated with prevention are minimized in response to economic factors but without considering the potential costs of treatment and compensation that may arise in future cases of infection of the staff or patients [ 2 , 21 , 22 ]. The latter also extends to accessing restrictions that make it difficult to directly consult specialists in the case of exposure to pathogenic agents, even though such exposure requires rapid preventive action [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%